Effect of spent engine oil pollution and liquid organic fertilizer application on soil chemical properties and nutrient contents of Maize (Zea Mays) - Elvis Kawedo; Godspower Omokaro; Kolawole Edomwonyi Law-Ogbomo (Sustinere: Journal of Environment and Sustainability, 2024)
A trial was conducted to evaluate the effect of spent engine oil (SEO), bio-treated with liquid organic fertilizer, on maize plant growth. The study utilized three concentrations of SEO (0.5 and 10% w/w) and four liquid organic fertilizers (water control, cattle dung, poultry manure and rabbit manure). These factors were arranged in a 3 × 4 factorial setup with three replications in a completely randomized design. Collected data included percentage moisture, dry weight, nutrient content and uptake, heavy metal concentration, and post-harvest soil chemical properties. Soil composite samples on physical and chemical analysis carried out show that the engine oil pollution negatively affected soil pH, total nitrogen, available phosphorus, and exchangeable cations, but it increased total organic carbon before maize cultivation. The percentage moisture and dry weight of the maize plant were not significantly (p > 0.5) influenced by engine oil pollution or liquid organic fertilizer application. N, P and Mg content of maize plant were significantly reduced by the engine oil pollution but significantly boosted by organic fertilizer application. Cr and Pb content of the maize were increased with engine oil concentration but decreased with liquid organic fertilizer. Nutrient uptake was decreased with increase in engine oil content but increased with liquid organic fertilizer application. At the end of the experiment, engine oil pollution significantly depressed pH, total N, available P and exchangeable cations, but increased organic C, total hydrocarbon, exchangeable Al and heavy metal content while it was opposite for liquid organic fertilizer. Our findings suggested that soils polluted with SEO should be corrected with the application of organic fertilizers.